2011
DOI: 10.1097/qad.0b013e3283427dcb
|View full text |Cite
|
Sign up to set email alerts
|

Low level of the K103N HIV-1 above a threshold is associated with virological failure in treatment-naive individuals undergoing efavirenz-containing therapy

Abstract: The presence of K103N mutant virus in plasma above 2000 copies/ml prior to therapy in treatment-naive individuals correlated with increased risk of virologic failure of these efavirenz-containing triple-drug regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
101
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 22 publications
3
101
1
Order By: Relevance
“…Using more-sensitive genotypic assays, different research groups (15,30,32,37,48,58,65) have reported higher proportions of transmitted DRM in ART-naive individuals. The clinical importance of these low-level DRM remains unclear, as they have been associated with clinical consequences in some (21,24,32,36,37,40,46,54,55,63,66,71) but not all (30, 47, 58) studies.Highly sensitive assays for detecting low-frequency DRM include point mutation assays and high-resolution sequencing techniques. Point mutation assays, such as allele-specific PCR, can detect DRM at frequencies as low as 0.01% of the sampled viral population (31,45,53,54), but they do not provide information about the sequence context surrounding a given DRM and may be prone to false positives at the lower level of detection (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using more-sensitive genotypic assays, different research groups (15,30,32,37,48,58,65) have reported higher proportions of transmitted DRM in ART-naive individuals. The clinical importance of these low-level DRM remains unclear, as they have been associated with clinical consequences in some (21,24,32,36,37,40,46,54,55,63,66,71) but not all (30, 47, 58) studies.Highly sensitive assays for detecting low-frequency DRM include point mutation assays and high-resolution sequencing techniques. Point mutation assays, such as allele-specific PCR, can detect DRM at frequencies as low as 0.01% of the sampled viral population (31,45,53,54), but they do not provide information about the sequence context surrounding a given DRM and may be prone to false positives at the lower level of detection (22).…”
mentioning
confidence: 99%
“…Using more-sensitive genotypic assays, different research groups (15,30,32,37,48,58,65) have reported higher proportions of transmitted DRM in ART-naive individuals. The clinical importance of these low-level DRM remains unclear, as they have been associated with clinical consequences in some (21,24,32,36,37,40,46,54,55,63,66,71) but not all (30, 47, 58) studies.…”
mentioning
confidence: 99%
“…For this reason, a series of ultrasensitive HIV-1-genotyping assays, based on deep sequencing (next-generation sequencing [NGS]), have been developed to detect drug-resistant HIV-1 variants at levels below 20% of the viral population in an infected individual (24,(28)(29)(30)(31). Several studies have associated early detection of these minority HIV-1 drug-resistant variants with subsequent treatment failure (32)(33)(34)(35)(36)(37); however, with the advent of single-pill once-a-day (QD) cART regimens, treatment failures in HICs are rare, and the relevance of minority members of the viral population to the ART outcome is still under debate (32,(38)(39)(40)(41).…”
mentioning
confidence: 99%
“…These undetected resistant associated mutations may cause suboptimal response to ART and lead to rapid emergence of HIV drug resistance, and can be implicated in early treatment failures. [116][117][118][119][120] Unequal exposure to antiretrovirals and treatment interruptions are thought to underlie the development of resistance in some patients. [121][122][123][124][125] Different rates of adherence to medications within a regimen (discordant adherence) combined with varied pharmacokinetics of the agents can lead to viral replication, and subsequent exposure to sub-optimal treatment regimens.…”
Section: Resistancementioning
confidence: 99%